The system of face detection based on OpenCV - Xianghua Fan; Fuyou Zhang; Haixia Wang; Xiao Lu (2012 24th Chinese Control and Decision Conference (CCDC), 2012)
Face detection technology has widely attracted attention due to its enormous application value and market potential, such as face recognition and video surveillance system. Real-time face detection not only is one part of the automatic face recognition system but also is developing an independent research subject. So, there are many approaches to solve face detection. Here the modified AdaBoost algorithm based on OpenCV is presented, and experiments of real-time face detecting are also given through two methods of timer and dual-thread. The result shows that the method of face detection with dual-thread is simpler, smoother and more precise.